PENGEMBANGAN JIWA WIRAUSAHA MELALUI PEMBUATAN BUSINESS PLAN MODEL CANVAS - Yuniarsih Yuniarsih; Tia Ristiawati; Viana Meilani Prasetio; Adinda Meidina Sari (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract The entrepreneurial spirit development program through the creation of a canvas model business plan is a program that aims to help students, alumni, and the general public to be able to build an entrepreneurial spirit by creating a work plan product that is mature for their entrepreneurship. This online P2M activity was attended by 106 participants consisting of lecturers, students, alumni and the general public who are interested in entrepreneurship. As can be seen from the results of the questionnaire, that 53.8% of the participants' business interests are culinary, while 30.8% are business in the education sector and the rest are interested in business in the fields of life style, culture and others. The response of the participants (100%) of this activity is useful to add insights in making a business plan with careful planning and can be a business solution in a pandemic like this. The results of business designs were competed, and those who succeeded in winning the competition were high school Japanese language teachers with the healty tempura business concept, and from the general public with the one stop Japanese learning center business concept. Abstrak Program pengembangan jiwa wirausaha melalui pembuatan business plan model canvas adalah program yang bertujuan untuk membantu mahasiswa, alumni, dan masyarakat umum untuk bisa membangun jiwa kewirausahaan dengan cara membuat suatu produk rencana kerja yang matang untuk wirausahanya. Kegiatan P2M secara daring ini dihadiri oleh 106 peserta yang terdiri dari dosen, mahasiswa, alumni dan masyarakat umum yang berminat terhadap wirausaha. Sebagaimana terlihat dari hasil angket, bahwa 53,8% bidang peminatan bisnis peserta adalah kuliner, sedangkan 30,8% adalah bisnis di bidang pendidikan dan sisanya berminat bisnis di bidang life style, budaya dan lainnya. Tanggapan peserta (100%) kegiatan ini bermanfaat menambah wawasan dalam membuat suatu rancangan bisnis dengan perencanaan yang matang dan bisa menjadi solusi bisnis di masa pandemi seperti ini. Hasil rancangan bisnis dikompetesikan, dan yang berhasil memenangkan lomba adalah guru bahasa Jepang SLTA dengan konsep bisnis healty tempura, dan dari masyarakat umum dengan konsep bisnis one stop Japanese learning center.